The Technology Acceptance Model (TAM): Case Study of Knowledge Sharing Among Lecturers at Universities in Vietnam - Sang, Do; Doan Quang Minh (Thailand and The World Economy, 2026)
This study research develops and tests a theoretical extension of the Technology Acceptance Model (TAM) that explains behavioral intention to use ICTs for knowledge sharing. In addition, there are different impacts on knowledge donating and knowledge collecting under the influences of demographic variables. The paper utilized structural equation modeling and cross-sectional design to test hypotheses in the proposed research model based on using data collected from 447 lecturers from 13 Vietnamese universities. The findings informed that (1) the TAM-based proposed scale has successfully explained factors predicting the use of ICTs in knowledge sharing among lecturers at universities in Vietnam. (2) the significant relationships among core components of TAM were found, except for the relationship between perceived usefulness and behavioral intention. (3) the finding of significant relationships between behavioral intention and using ICTs in knowledge sharing was reported. In addition, there are different impacts on knowledge donating and knowledge collecting under the influences of demographic variables (age, expertise type). New variables should be explored to better explain the behavioral intention of lecturers to use ICTs for knowledge sharing. Further research should test mediating roles of knowledge sharing’s constituents by adding new variables such as knowledge self-efficacy, job involvement, trust, attitude, motivation, barriers, and the like. This study provides a theoretical basis, which can be used to analyze relationships among knowledge-sharing factors and to discuss the implications of these factors for developing universities’ strategies that encourage and foster knowledge sharing among lecturers at universities in Vietnam. Most of the studies on knowledge sharing have been conducted in an organizational context. Only limited work has been done on the knowledge sharing among university lecturers. This study contributes to knowledge-sharing literature that suffers from a paucity of research on the empirical examination of this subject.